2012
DOI: 10.1007/jhep06(2012)061
|View full text |Cite
|
Sign up to set email alerts
|

Algebras for amplitudes

Abstract: Tree-level amplitudes of gauge theories are expressed in a basis of auxiliary amplitudes with only cubic vertices. The vertices in this formalism are explicitly factorized in color and kinematics, clarifying the color-kinematics duality in gauge theory amplitudes. The basis is constructed making use of the KK and BCJ relations, thereby showing precisely how these relations underlie the color-kinematics duality. We express gravity amplitudes in terms of a related basis of color-dressed gauge theory amplitudes, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
184
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 147 publications
(185 citation statements)
references
References 80 publications
0
184
0
1
Order By: Relevance
“…Both the color-kinematics duality and the double copy are well understood at tree level [12,21,[26][27][28][29][30][31]. The recently developed formalism of the scattering equations has JHEP01(2016)171 brought a new insight into these structures [32][33][34][35][36][37].…”
Section: Bcj Duality and Double Copymentioning
confidence: 99%
“…Both the color-kinematics duality and the double copy are well understood at tree level [12,21,[26][27][28][29][30][31]. The recently developed formalism of the scattering equations has JHEP01(2016)171 brought a new insight into these structures [32][33][34][35][36][37].…”
Section: Bcj Duality and Double Copymentioning
confidence: 99%
“…In general, such choice of numerators is non-unique, but non-trivial to find. By now, various algorithms have been described for finding BCJ numerators; see, for example, [23,[31][32][33]37]. We shall discuss below how the scattering equations are naturally associated with a certain set of numerators.…”
Section: Jhep03(2014)110mentioning
confidence: 99%
“…We see this result as a direct consequence of the fact, proven in [30], that the Parke-Taylor factors arising from each solution of the scattering equations (to be reviewed next) satisfy the so-called BCJ relations. Explicit constructions to invert the linear problem and generate BCJ numerators for amplitudes satisfying the BCJ relations were presented in [31][32][33]. In this work, we provide a canonical set of BCJ numerators which can be constructed directly from the vertex configuration of a trivalent graph, based on algebraic structures naturally associated to the scattering equations.…”
Section: Introductionmentioning
confidence: 99%
“…An explicit construction was given by Mafra, Schlotterer and Stieberger using the pure spinor language [34]. Alternatively, it was shown that the kinematic factors can be interpreted in terms of diffeomorphism algebra [23,[35][36][37]. In a series of recent papers [38][39][40] another interesting construction was provided by Cachazo, He and Yuan (CHY) using the solutions to the scattering equations.…”
Section: Jhep08(2014)098mentioning
confidence: 99%
“…Instead of attempting to decipher the analytic structure responsible for the possible algebraic behavior, another line of thoughts is to solve the kinematic numerators reversely in terms of scattering amplitudes, and indeed, it was discussed in [36,41] that such expression for the numerators can always be derived in suitable basis. A technical issue lies with this approach is that because of the complexity involved, along with the ambiguity introduced by generalized gauge invariance, it is practically difficult to write down an analytic expression for generic numerator.…”
Section: Jhep08(2014)098mentioning
confidence: 99%